Bad Bank(s) and the recapitalisation of the banking sector - Dorothea Schäfer; Klaus F. Zimmermann (Intereconomics, 2009)
With banking sectors worldwide still suffering from the effects of the financial crisis, public discussion of plans to place toxic assets in one or more bad banks has gained steam in recent weeks. The following paper presents a plan how governments can effi ciently relieve ailing banks from toxic assets by transferring these assets into a publicly sponsored workout unit, a so-called bad bank. This plan effectively addresses three key challenges. It provides for the transparent removal of toxic assets and gives the banks a fresh start. At the same time, it offers the chance to keep the cost to taxpayers low. In addition, the risk of moral hazard is curtailed.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: 330